The Local Online Media Professionalism Over Candidate Framing Inside Pacitan Election 2020 - Agoes Hendriyanto; Andrik Purwasito; Wakit Abdullah Rais; Sri Hastjarjo (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
The Pacitan Local Leaders Election (Pilkada Pacitan) 2020 must both run democratically and prioritize the citizens’ health in the time of the Covid-19 pandemic. Besides, Pacitan local online media are firstly allowed under regulations (PKPU No 13, 2020) to achieve the success of the elections. From this first-time involvement, the local online media are dealt with various interests trying to attract journalists or online media to stand with one or the other candidate pairs. To meet the purpose, the researchers employed qualitative research methods using framing analysis. In this case, Edelman framing analysis, with categorization choice by highlighting and eliminating other aspects, aims at building an opinion. In conformity with the results, the local online media are not neutral. Further, the news text framing of the online media professionalism in reporting the Pacitan Pilkada was as follows: 1) political culture in Pacitan, 2) ethical competence, 3) legal competence, 4) knowledge competence. Those competencies must be possessed by a journalist. Even more, they were carrying out political activities such as the 2020 Pilkada. The professionalism of journalists was necessarily needed, especially in Indonesia’s democratic party implementation to elect legislative and executive leaders who were truly coming from the people’s soul.